Factors associated with treatment response in chronic nonbacterial osteomyelitis at a single center: a retrospective cohort study - Katherine D. Nowicki; Nathan D. Rogers; Carson L. Keeter; Nathan J. Donaldson; Jennifer B. Soep; Yongdong Zhao (Pediatric Rheumatology Online Journal)
Abstract Background NSAIDs are commonly used as first line therapy in chronic nonbacterial osteomyelitis (CNO) but are not effective for all patients. The objective of this study was to identify clinical variables associated with NSAID monotherapy response versus requiring second-line medication in a single-center cohort of patients with CNO. Methods The charts of children with CNO who attended a CNO clinic at a quaternary care center between 1/1/05 and 7/31/21 were retrospectively reviewed. Patients were divided into 3 groups: NSAID-short (NSAID monotherapy for 3 to < 7 months), NSAID-long (NSAID monotherapy for ≥ 7 months), or second-line treatment. Patients were also categorized by which bodily regions were affected by CNO. Multiple linear and logistic regression models were constructed to predict total NSAID monotherapy days and the odds of needing second-line treatment, respectively. These models were optimized using variable combinations that minimized multicollinearity and maximized predictive power, as indicated by minimized AIC values. Results One-hundred-sixty-four patients fulfilled inclusion criteria. Thirty-two patients were in the NSAID-short group, 62 in the NSAID-long group, and 70 in the second-line treatment group. Comparing the two NSAID groups showed that patients with unifocal disease at diagnosis required 47% fewer days of NSAIDs than those with multifocal disease. Results from logistic regression indicated that for each additional region affected, the odds of needing second line treatment increased by 1.94 times (p = 0.01) and that patients with symmetric bone lesions were 6.86 times more likely to require second-line treatment (p < 0.001). Conclusions Patients with unifocal CNO involvement at diagnosis were more likely to require shorter NSAID treatment. Patients with more regions affected and those with symmetric bone lesions were more likely to require second-line treatment.